Near-Infrared Photobiomodulation of Living Cells, Tubulin, and Microtubules In Vitro - Staelens, Michael; Di Gregorio, Elisabetta; Kalra, Aarat P.; Le, Hoa T.; Hosseinkhah, Nazanin; Karimpoor, Mahroo; Lim, Lew; Tuszyński, Jack A. (Frontiers in Medical Technology, 2022)
We report the results of experimental investigations involving photobiomodulation (PBM) of living cells, tubulin, and microtubules in buffer solutions exposed to near-infrared (NIR) light with a wavelength of 810 nm pulsed at a frequency of 10 Hz. In the first group of experiments, we measured changes in the alternating current (AC) ionic conductivity in the 50–100 kHz range of HeLa and U251 cancer cell lines as living cells, exposed to PBM for 60 minutes, and observed increased resistance compared to the control experiments. In the second group of experiments we investigated the stability and polymerization of microtubules under exposure to PBM. The protein buffer solution used was BRB80/PEM. Exposure of TaxolTM-stabilized microtubules (∼ 2 μM tubulin) to the LED at 810 nm, with a power density of 25 mW/cm2 pulsing at 10 Hz for 120 minutes, resulted in gradual disassembly of microtubules observed in fluorescence microscopy images. These results were compared to controls where microtubules remained stable. In the third group of experiments we performed turbidity measurements (absorbance readings at 340 nm) throughout the tubulin polymerization process to quantify the rate and amount of polymerization for exposed versus unexposed tubulin samples, using tubulin re-suspended to final concentrations of ∼ 22.7 μM and ∼ 45.5 μM in a mixture of G-PEM buffer (final concentration of 1 mM GTP) and microtubule cushion buffer (10% the final volume). Compared to the unexposed control samples, absorbance measurement results demonstrated a slower rate and reduced overall amount of polymerization in the less concentrated tubulin samples exposed to PBM for 30 minutes with the same parameters mentioned above. Paradoxically, the opposite effect was observed in the 45.5 μM tubulin samples, demonstrating a remarkable increase in the polymerization rates and total polymer mass achieved after exposure to PBM. These results on the effects of PBM on living cells, tubulin, and microtubules are novel, further validating the modulating effects of PBM and contributing to designing more effective PBM parameters. Potential consequences for the use of PBM in the context of neurodegenerative diseases are discussed.